Effect of sex differences in antinociceptive, antipyretic, hypoglycemia, hepatoprotective and antidiarrheal activities in mice model - Irin Karim; Roni Roy; Md Rafiul Hoque; Sazzad Hosen; Tanaya Bhowmik; Israt Jahan Liya; Afroza Akter; Mohammad Anwarul Basher (GarVal Editorial Ltda., 2020)
Context: The use of animal models is a longstanding practice in biological research. Among different models, the mouse is the most widely used and accepted model. In designing the mouse model, a male mouse is generally preferred over a female to avoid the effect of changing hormonal state in females. However, it is not known whether mouse sex affects all experiments. Aims: To determine the effect of mouse sex on pharmacological responses in antinociceptive, antipyretic, hypoglycemia, hepatoprotective and antidiarrheal experiments. Methods: Antinociceptive study was performed by three different experiments. An antipyretic experiment was performed by yeast induced hyperthermia test. The effect on hypoglycemic response was assessed by an oral glucose tolerance test. The effect on the hepatoprotective study was evaluated by carbon tetrachloride-induced liver damage. The antidiarrheal study was conducted by a castor oil-induced diarrhea test. Results: Antinociceptive studies demonstrated mixed effects. Hot plate test showed significant differences; the licking test showed variation only in the late phase, while no significant variation was observed. In the antipyretic experiment, female mice showed higher body temperature in both control and standard that varied significantly with male mice. Hypoglycemia and hepatoprotective tests did not show significant variation between sexes; however, liver enzymes levels were found higher in males while the percentage liver weight was higher in females. In the antidiarrheal test, the male mouse was observed to have higher responses than the female. Conclusions: Antinociceptive and antipyretic investigations should be performed separately on both male and female mice. On the other hand, hypoglycemic, hepatoprotective and antidiarrheal tests can be conducted on any mouse sex, and findings on particular sex can be extrapolated to the opposite sex.